2015
DOI: 10.1007/s13277-015-3839-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of KPNβ1 in gastric cancer cell promotes tumor cell proliferation and predicts poor prognosis

Abstract: KPNβ1, also known as importin β, P97, is reported as one of soluble transport factors that mediates transportion of proteins and RNAs between the nucleus and cytoplasm in cellular process. Recent studies show that KPNβ1 is a tumor gene which is highly expressed in several malignant tumors such as ovarian cancer, cervical tumor, neck cancer, and lung cancer via promoting cell proliferation or inhibiting cell apoptotic pathways. However, the the role of KPNβ1 in gastric cancer remains unclear. In this study, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…CRM1, for example, has been identified as a suitable marker for poor prognosis in gastric, ovarian, pancreatic and brain cancer as well as in acute myeloid leukemia and osteosarcoma [ 35 , 36 , 37 , 38 , 39 , 40 ]. Moreover, importin β1 has been identified as marker for poor prognosis in gastric cancer [ 41 ], while the nuclear expression of the export receptor CAS associates with lower overall survival and highly aggressive tumors in bladder and ovarian cancer, respectively [ 42 , 43 ].…”
Section: Pathophysiological Relevance Of Nucleocytoplasmic Transpomentioning
confidence: 99%
“…CRM1, for example, has been identified as a suitable marker for poor prognosis in gastric, ovarian, pancreatic and brain cancer as well as in acute myeloid leukemia and osteosarcoma [ 35 , 36 , 37 , 38 , 39 , 40 ]. Moreover, importin β1 has been identified as marker for poor prognosis in gastric cancer [ 41 ], while the nuclear expression of the export receptor CAS associates with lower overall survival and highly aggressive tumors in bladder and ovarian cancer, respectively [ 42 , 43 ].…”
Section: Pathophysiological Relevance Of Nucleocytoplasmic Transpomentioning
confidence: 99%
“…Thus, the identification of genes and pathways involved in and/or altered in this process will not only improve our understanding of cancer initiation and development, but will also help in the identification of novel anticancer drug targets. Previous studies have revealed Karyopherin β1 (Kpnβ1), the primary nuclear import protein, to be significantly overexpressed in a variety of cancer types including cervical [ 10 ], gastric [ 30 ], and breast cancers [ 13 ]. Furthermore, these studies reveal that inhibition of Kpnβ1 expression leads to cancer cell death, while inhibition in non-cancer cells has only a minor effect on cell viability [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that Impβ expression is increased in several malignant tumors such as cervical tumors and malignant peripheral nerve sheath tumors (MPNSTs) as well as in breast, gastritic, neck, lung and ovarian cancers [ 145 , 158 , 159 , 160 , 161 , 162 ]. Impβ up-regulation has been shown to promote cell proliferation in gastritic and cervical cancer cells [ 145 , 158 ]. Also, one of the adaptor molecules Karyopherin α2 bridging the interaction between Impβ and NLS-bearing cargo is a potential biomarker in multiple cancers reviewed in [ 163 ].…”
Section: The Nucleocytoplasmic Transport Machinerymentioning
confidence: 99%